Factors related to the disability burden in people with suicidal attempts attended in the public health care service network of Santiago de Cali (2013)
Introduction According to the World Health Organization (WHO), the aftermaths of suicide attempts are the sixth leading cause of poor health and disability in the world. Object Establish the level of disability and related factors in terms of restrictions regarding participation and activity limitations in cases of suicidal attempts attended by the Public Service Network Health of Santiago de Cali, from September 2009 to June 2010. Methodology A cross-section, observational study was applied to 126 people between 15 and 65 who had attempted suicide and were treated at the Public Health Service in Santiago de Cali. A Spanish version of the Disability Assessment Scale of the World Health Organization Results 30 disability-adjusted life years (DALYs) were calculated together with a disability prevalence of 95.3%. 4.6% of the sample did not show disability while 41.27% had mild disability, 38.1%, moderate disability, and 15.87%, severe disability. Factors related with disability were: Age, occupation, presence of mental illness, current depressive symptoms, lethal methods, use of psychiatric drugs, activity limitations, participation restrictions and lack of religious practice. Conclusions The prevalence of disability in people who have committed suicidal attempts treated at the public health services in Santiago de Cali, was 95.3%. The results are consistent with the study of global burden of disease that establishes a high score for mental disorders in suicidal attempts. The presence of a deficiency after the suicide attempt increases the burden of disability.